Matching for Risk-Taking: Overconfident Bankers and Government-Protected Banks - Andreas Haufler; Bernhard Kassner (CESifo GmbH, 2024)
We set up a simple theoretical model in which banks with varying degrees of government support are matched with CEOs that have different degrees of overconfidence. The channel through which the matching occurs is the share of bonus payments offered by banks in their profit-maximizing contracts. This yields a sequence of hypotheses: banks with more government support incentivize their CEOs more and this disproportionately attracts overconfident CEOs. In equilibrium this in turn leads to an assortative matching between overconfident managers and banks with a larger bailout probability. We then test the hypotheses derived from this model for U.S. data spanning both the Great Financial Crisis and the Covid Crisis. Our results confirm the hypotheses from our theoretical model for normal years, but not during crises and periods of enhanced regulation. In normal years, therefore, overconfident bankers are indeed matched with government-protected banks, with cumulative effects on the degree of risk-taking.
Keywords: G21; G28; H32; 330; matching; overconfidence; incentive contracts